2015
DOI: 10.2147/rru.s58974
|View full text |Cite
|
Sign up to set email alerts
|

Management of erectile dysfunction post-radical prostatectomy

Abstract: Radical prostatectomy is a commonly performed procedure for the treatment of localized prostate cancer. One of the long-term complications is erectile dysfunction. There is little consensus on the optimal management; however, it is agreed that treatment must be prompt to prevent fibrosis and increase oxygenation of penile tissue. It is vital that patient expectations are discussed, a realistic time frame of treatment provided, and treatment started as close to the prostatectomy as possible. Current treatment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…[ 11 ] Although long-term results are good, the rate of postoperative ED was reported to be 14%–90% depending on the surgical approach and the surgeon's experience. [ 12 14 ] In addition, Boylu et al [ 15 ] reported that the rate of ED after robot-assisted laparoscopic RP was 83% in the 12th month. Neuropraxia is the most common cause of postoperative ED in patients undergoing RP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] Although long-term results are good, the rate of postoperative ED was reported to be 14%–90% depending on the surgical approach and the surgeon's experience. [ 12 14 ] In addition, Boylu et al [ 15 ] reported that the rate of ED after robot-assisted laparoscopic RP was 83% in the 12th month. Neuropraxia is the most common cause of postoperative ED in patients undergoing RP.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, pro-apoptotic and pro-fibrotic changes in the corpora cavernosum are considered responsible for the formation of RP related ED. [ 12 , 13 ] Autonomic fibers are carried to the penis by the CN which has a positive neural nitric oxide synthase activity. [ 16 , 17 ] Some anastomosing fibers are between terminal CNs and the DPN, below the pubic arch in the penile hilum region.…”
Section: Discussionmentioning
confidence: 99%
“…Various degrees of cavernous nerve damage always occur during prostatectomy and even nerve-sparing surgery is no exception. Apart from mechanical injury of the pelvic plexus and its branches postprostatectomy, ED is a result of developing fibrosis due to prolonging penile flaccidity (77). The desired effects of potential stem cell-based therapy are expected to reverse the structural changes leading to ED and to mitigate patient dependence on the transitory effect of PDE5 inhibitors.…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…Medications such as prostaglandin E1 (PGE1) muscle relaxant and erectile stimulant standalone or in combination with papaverine, phentolamine, and vasoactive intestinal peptide (VIP) are reasonable first-line ED therapies, which are administered through penile corpora [4,10,13]. This therapy is considered as an alternative among those non-respondent to PDE5I treatment [14].…”
Section: Intracavernosal Medications and Intraurethral Suppositoriesmentioning
confidence: 99%